A True Experimental Study to Evaluate the Effectiveness of Structured Teaching Programme on Knowledge Regarding III – Effects of Alcohol Consumption among Adolescents in Selected Senior Secondary School at Panipat Haryana (International Journal of Nursing Education, 2019)
One of the major public health issues worldwide among senior secondary school childrens is alcohol consumption. However, the extent of consumption among senior secondary school students and their understanding of its ill effects on health remain relatively unknown in many cities of Haryana. This study aim to evaluate the effectiveness of structured teaching programme on knowledge regarding ill effects of alcohol consumption, among adolescents in senior secondary schools at Panipat, Haryana. This study was based on quantative approach, the researcher used true – experimental design. The sampling method adopted was Simple random method and total sample size was 60 (30-experimental group, 30- control group) . Data collection method was self reporting questionnaire. The result of the study shows, in experimental group the pre-test mean score was 12.47 and the post-test mean score was 22.90, the standard deviation score in pre test and post test of experimental group was 2.34 and 2.28 respectively, the paired ‘t’ test value was 16.855 at which was higher than Table Value (2.05). Hence, null hypothesis was rejected and concluded in experimental group. There was significant increase in knowledge after STP on ill effects of alcohol consumption. The study result suggested that educating adolescents on ill effects of alcohol consumption will be effective in increasing their knowledge on the same.